2014
DOI: 10.4149/bll_2014_089
|View full text |Cite
|
Sign up to set email alerts
|

Impact of glycemic control on advanced glycation and inflammation in overweight and obese patients with type 2 diabetes mellitus

Abstract: Abstract:Aim: In this study we tried to investigate the impact of glycemic control on parameters of glycation and infl ammation in overweight and obese patients with type 2 diabetes mellitus. Patients and methods: Markers of glycation (HbA 1c , AGEs; measured by HPLC and spectrofl uorimetry, resp.) and infl ammatory markers (IL-6, IL-8, TNF-α, MCP-1; measured by xMAP technology) were assessed in 69 patients with T2DM, of whom 32 were patients were with poor glycemic control (PGC group), 37 patients were with g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 92 publications
3
8
0
Order By: Relevance
“…TNF- α and MCP-1 are two proinflammatory cytokines that can be released by adipose tissue. In the current study, the results showed that the visceral adipose tissue expression levels of TNF-α and MCP-1 in normal group were significantly lower than those in obesity and T2DM groups ( P < 0.01), which were consistent with the previous study where TNF- α and MCP-1 were elevated in poor glycemic control and good glycemic control overweight and obese patients [ 16 ], suggesting that the immune response of visceral adipose tissue was changed during the occurrence of obesity and T2DM.…”
Section: Discussionsupporting
confidence: 92%
“…TNF- α and MCP-1 are two proinflammatory cytokines that can be released by adipose tissue. In the current study, the results showed that the visceral adipose tissue expression levels of TNF-α and MCP-1 in normal group were significantly lower than those in obesity and T2DM groups ( P < 0.01), which were consistent with the previous study where TNF- α and MCP-1 were elevated in poor glycemic control and good glycemic control overweight and obese patients [ 16 ], suggesting that the immune response of visceral adipose tissue was changed during the occurrence of obesity and T2DM.…”
Section: Discussionsupporting
confidence: 92%
“…In principle, obesity and diabetes have been associated with matrix stiffening that may be at least partially mediated by AGE cross-links. 49,50 Emission from such cross-links is more consistent with the excitation/emission wavelengths of our study, than LOX-mediated cross-links. However, the impact of AGE cross-links on mechanical properties may be highly dependent on the type of tissue and the nature of the cross-links.…”
Section: Conclusion and Discussionsupporting
confidence: 87%
“…Diabetes mellitus is a serious global health problem resulting from insulin insuffi ciency or ineffi ciency which, its prevalence is increasing dramatically, and due to the rising rate of obesity and sedentary lifestyle, about 552 million people are estimated to be suffering from diabetes mellitus worldwide by 2030 (1,2). Diabetes-induced hyperglycemia and the corresponding glucotoxicity result in macro and microvascular complications such as diabetic neuropathy, nephropathy, retinopathy, and cardiomyopathy (3).…”
Section: Introductionmentioning
confidence: 99%